Management Fisioterapi Pada Post Ligament Anterior Cruciatum Recontruction (ACLR) Fase 1 Di RSD KRMT Wongsonegoro, Semarang: Case Report - Raveena Wulan Octavia; Isnaini Herawati; Halim Mardianto (jurnal ABDIMAS Indonesia, 2024)
Background: The ACL is a ligament in the knee joint which functions to stabilize the tibia when moving forward and in rotational movements of the knee joint. Treatment for Anterior Cruciate Ligament (ACL) injuries can be done with several procedures, namely reconstructive and conservative. ACL reconstruction is a surgical procedure that replaces the injured ACL with a tendon graft because the ACL does not heal after injury due to insufficient vascularization. Common conditions after undergoing ACL reconstruction surgery are complication problems such as experiencing knee stiffness which includes swelling, pain, limited Range of Motion (ROM), especially in extension, decreased muscle strength and decreased proprioception. Objective : To determine the effectiveness of providing exercise in handling post-operative cases of phase 1 ACL surgery. Method: This study used the Case Report method which was carried out at RSD KRMT Wongsonegoro, Semarang in January 2024. The patient was a 20 year old male, diagnosed with Post Op. ALCR phase 1. Results & Discussion: After being given physiotherapy intervention for 3 meetings. With each therapy, it appears that there continues to be improvement. Can increase joint range of motion, increase knee flexor muscle strength, reduce perceived pain, and change segment circumference. Results: Based on the research that has been carried out, the results showed that providing physiotherapy intervention can be effective in phase 1 ACLR cases.